The washback effect of examinations on teaching and learning English in a preparatory school: A study in a foundation university - Bulut, Mehmet Akın (My University, 2018)
Used and explained as the effect of tests and exams on learning and teaching and basically categorized as positive and negative effect, ‘Washback’ in this study aims to find out the effects of a) quizzes, b) midterm, c) final and d) English Preparatory School exit test PTE (Pearson Test of English) on learning and teaching in Ibn Haldun University Preparatory School. To this end, 135 students and 10 instructors took part in this study. As a first step, as a pilot study, a 40-item questionnaire was directed to 28 students, and in the final mode it was reduced to 30 questions and administered to 110 students. To strengthen the reliability and validity of the study, 10 randomly selected students were interviewed using a 5-item structured interview. In order to find out teachers’ opinions about the subject matter, 10 instructors were intervieved using a 5-item interview. After the analysis of this data, it was found that exams and tests have both positive and negative effects on learning and teaching. These findings present the managers, instructors and testing office staff/test developers significant data and inference in order to spot the weaknesses in the system and to reinforce the good points with the purpose of increasing the positive washback effects of tests.

estlerin öğrenme ve öğretme üzerine etkisi anlamında kullanılan ve olumlu ve olumsuz etkiler olarak temelde iki kategori altında incelenen ‘Geri Etki’, İbn Haldun Üniversitesi Hazırlık Sınıflarındaki a) quizler, b) ara sınav, c) final sınavı ve d) bilgisayar üzerinden yapılan Hazırlık geçme sınavı PTE (Pearson Test of English) ‘nin öğrenme ve öğretme üzerine etkisini bulmayı amaçlamaktadır. Bu amaçla, 135 öğrenci, 10 okutman bu çalışmada yer almıştır. İlk etapta 28 öğrenciye 40 soruluk anketin pilot çalışması uygulanmış ve son halinde 30 soruya indirilierek 110 öğrenci ile anket çalışması gerçekleştirilmiştir. Anket sonucunun tutarlılığını sağlamlaştırmak amacıyla rastgele seçilen 10 öğrenci ile de 5 sorunun yöneltildiği mülakat yapılmıştır. Konuya dair görüşlerine başvurulmak üzere 10 okutman ile yine 5 soru içeren görüşmeler gerçekleştirilmiştir. Anketler için SPSS 25 ve görüşmeler için de içerik analizi yapılmıştır. Elde edilen nihai veriler analiz edilmiştir. Sonuçlar sınavların öğrenme ve öğretme üzerinde hem olumlu hem olumsuz etkileri göstermektedir. Sonuçlar, yöneticilere, öğretmenlere ve test geliştiricilere, sistemin zayıf yanlarının bulunması ve güçlendirilmesi ile olumlu etkilerin artırılması yönünde çok önemli bilgiler ve çıkarımlar sunmaktdır.
Hazırlık okulu sınavlarının ingilizce öğretme ve öğrenme üzerindeki geri etkisi: Bir vakıf üniversitesi örneği